Adult education needs inventory: Construction and application - Ślósarz, Luba; Błaszczyński, Kamil; Švecová, Magdaléna; Kobylarek, Aleksander (Frontiers in Psychology, 2022)
Background: The article presents the psychometric parameters and implementation of the AENI (The Adult Education Needs Inventory) questionnaire, which is designed to measure the key competences of adult educators. It was constructed on the concept of key competences as proposed by the Council of the European Union. This model of competences is inscribed in the concept of lifelong learning and does not concentrate on the compensatory functions of the competences but merely promotes the insight of educators into their self-development. The study aimed to This article presents the construction process and psychometrical properties of AENI. Material and methods: The reliability of the test is confirmed by the inter-correlated results. The accuracy of the questionnaire was confirmed through principal component analysis (PCA). Apart from this, the accuracy of the theory was verified by a correlation between AENI and the Social Skills Profile (PROKOS), which measures the level of such social skills as assertiveness, cooperativeness, sociability, social resourcefulness, and social activeness. To check the accuracy of the theory, hypotheses were formulated which were related to both the correlated overall results (AENI and PROKOS) and the chosen scales. Results: Six areas of need in development were distinguished: communication skills, multilingual and multicultural skills, digital skills, entrepreneurial skills, openness to science and culture, and social and civic skills. A low result on the scale indicates a need to develop a given skill because the respondent's skills are weak. Such information is vital for employers and educators who wish to diagnose the areas that need improvement. The measures of reliability and accuracy allow us to state that the questionnaire possesses acceptable psychometrical factors. This study contains propositions for further improvement of the questionnaire and a key to interpreting the research results. Conclusions: AENI questionnaire is a reliable research tool that can be used to assess the competences of adult educators. Also, it can be considered a voice of discussion regarding the necessity of raising the quality of education and raising the awareness of the education needs of individual adult educators and organizations that benefit from their services.